Tin plating in acid Sn(II) gluconate solutions containing excess of sulphate. (1st July 2013) - Survila, A; Mockus, Z; Kanapeckaitė, S; Stalnionis, G; Juškėnas, R
Abstract : Voltammetry, electrochemical impedance spectroscopy, SEM and XRD techniques were applied to study tin plating in acid 0·01M Sn(II) solutions containing different amounts (0·02-0·1M) of gluconate and 0·5M Na2 SO4 . Solution pH is the main factor that governs the rate of Sn(II) reduction. An increase in pH from 2 to 5 results in a 100-fold growth in electrode impedance and a four-fold reduction in limiting current density. Spongy tin deposits are obtained in the ligand insufficient solutions at low cathodic polarisations ∆ E . To obtain compact fine grained tin coatings, ∆ E and/or the gluconate concentration should be correspondingly increased. Sn(II) reduction proceeds under conditions of strong inhibition involving destructive ligand chemisorption and incorporation of its fragments into deposits.